2016
DOI: 10.2217/bmm-2016-0169
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Expression of Thyroid Hormone Receptor-Interacting Protein 13 Drives Tumorigenesis and Affects Clinical Outcome

Abstract: TRIP13 is highly expressed in multiple tumors and may be used as a potential prognostic marker and therapeutic target.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…TRIP13 was originally recognized as a participant in meiotic recombination, spindle assembly checkpoint, and DNA repair [15][16][17]. Actually, as a AAA ATPase, which can facilitate the assembly or degradation of protein complexes, TRIP13 has been reported to be significantly up-regulated in multiple types of tumors and involved in tumorigenesis by binding various proteins [18,19]. Bannerjee and his colleagues first verified that TRIP13 is an oncogene and demonstrated that it induces chemoresistance in head and neck cancer by interacting with the DNA-PK complex to enhance non-homologous end joining [17].…”
Section: Discussionmentioning
confidence: 99%
“…TRIP13 was originally recognized as a participant in meiotic recombination, spindle assembly checkpoint, and DNA repair [15][16][17]. Actually, as a AAA ATPase, which can facilitate the assembly or degradation of protein complexes, TRIP13 has been reported to be significantly up-regulated in multiple types of tumors and involved in tumorigenesis by binding various proteins [18,19]. Bannerjee and his colleagues first verified that TRIP13 is an oncogene and demonstrated that it induces chemoresistance in head and neck cancer by interacting with the DNA-PK complex to enhance non-homologous end joining [17].…”
Section: Discussionmentioning
confidence: 99%
“…TRIP13 has been suggested to be overexpressed in multiple tumors and function as oncogene in carcinogenesis. 14 Interestingly, we observed that TINCR expression was markedly negatively correlated with TRIP13 mRNA expression in 374 prostate cancer tissue samples from TCGA database ( r =−0.554, P <0.001, Figure 3A ). Furthermore, the relationship of TINCR expression with TRIP13 mRNA and protein was explored in prostate cancer tissues.…”
Section: Resultsmentioning
confidence: 90%
“…TRIP13 is identified as an oncogene, whose overexpression can lead to many human cancers. A large number of studies suggested that TRIP13 gene is highly expressed in head and neck cancer, prostate cancer, lung cancer and breast cancer tissues and is closely associated with colorectal cancer, gastric cancer [16, 21, 2326].…”
Section: Introductionmentioning
confidence: 99%